Tantalum-specific contrast-to-noise ratio or conventional detector dose-driven exposure control in angiography: radiation dose and image quality evaluation in a porcine model - Thomas Werncke; Timo Christian Meine; Jan B. Hinrichs; Sabine K. Maschke; Lena Sophie Becker; Inga Brüsch; Regina Rumpel; Frank K. Wacker; Bernhard C. Meyer (European Radiology Experimental, 2022)
Abstract Background The aim of this animal study was to compare the fluoroscopic image quality (IQ) and radiation dose between a tantalum (Ta)-specific contrast-to-noise ratio-driven exposure control (Ta-CEC) and a detector dose-driven exposure control (DEC) in abdominal angiography. Methods Nine angiography scenarios were created in seven anaesthetised pigs using Ta-based embolisation material during percutaneous liver and kidney intervention. Fluoroscopic images were acquired using three DEC protocols with different dose levels and Ta-CEC protocols with different IQ levels, sampled in small steps. Polymethyl-methacrylate and aluminium plates were used to simulate attenuation of three water equivalent thicknesses (WET). Three blinded readers evaluated the IQ of DEC and dose equivalent Ta images and selected the Ta-IQ equivalent image corresponding to the DEC image. Results Interobserver agreement for the IQ assessment was 0.43 for DEC, 0.56 for Ta-CEC and for the assessment of incident air kerma at the interventional reference point (K a,r) for the Ta-IQ equivalent image 0.73. The average IQ of the dose equivalent Ta images was superior compared to the DEC images (p < 0.001) and also for every WET (26, 31, or 36 cm) and dose level (p ≤ 0.022). The average K a,r for the Ta-IQ equivalent images was 59 ± 16% (mean ± standard deviation) lower compared to the DEC images (p < 0.001). Conclusions Compared to DEC, Ta-CEC significantly improved the fluoroscopic depiction of Ta, while maintaining the K a,r. Alternatively, the K a,r can be significantly reduced by using Ta-CEC instead of DEC, while maintaining equivalent IQ.